2012
DOI: 10.1111/j.1432-2277.2012.01457.x
|View full text |Cite
|
Sign up to set email alerts
|

Predicting severity and clinical course of acute rejection after liver transplantation using blood eosinophil count

Abstract: Summary Acute cellular rejection remains an important source of morbidity after liver transplantation, particularly if rejection is moderate or severe, as this usually is treated. Currently liver biopsies are seldom performed, so diagnostic noninvasive markers would be useful. We evaluated 690 consecutive first liver transplant patients to assess whether peripheral eosinophilia could predict moderate‐severe rejection and its course. A protocol biopsy was performed 6 ± 2.5 days after transplant. A second biopsy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 23 publications
(38 reference statements)
1
44
0
1
Order By: Relevance
“…[32][33][34][35] Nagral et al 36 showed that an eosinophil count 4400/mm 3 could predict rejection beginning 2 days before biopsy. These studies, however, used the maximum eosinophil count, focusing on an acute rise in the eosinophil count at the time of ACR, rather than examining the "average" eosinophil counts longitudinally.…”
Section: Figurementioning
confidence: 99%
“…[32][33][34][35] Nagral et al 36 showed that an eosinophil count 4400/mm 3 could predict rejection beginning 2 days before biopsy. These studies, however, used the maximum eosinophil count, focusing on an acute rise in the eosinophil count at the time of ACR, rather than examining the "average" eosinophil counts longitudinally.…”
Section: Figurementioning
confidence: 99%
“…As an alternative, detection of putative rejection episodes was based on biochemical surveillance. It was shown that biochemical parameters are of limited sensitivity and specificity in the detection of liver graft rejection episodes . Therefore, less severe and transient rejection episodes during the study period cannot be completely excluded.…”
Section: Discussionmentioning
confidence: 99%
“…Although acute liver rejection is a histological diagnosis and a liver biopsy is considered essential when evaluating the efficacy of immunosuppressors, the use of noninvasive methods for the diagnosis of rejection can be potentially useful in clinical practice, particularly considering the well‐known limitations of liver biopsy . In fact, several studies have addressed the role of routine biological markers, such as blood eosinophils, bilirubin, GGT, or AP, in the diagnosis and prognosis of ACR and also in their ability to predict response to treatment . However, none of these biomarkers has shown enough accuracy to be incorporated into clinical practice as a reliable tool, even to select patients to undergo liver biopsy for a suspect of rejection.…”
Section: Discussionmentioning
confidence: 99%